Opportunities and Challenges to Strengthen the Role of Non-Judge Mediators in Realizing Humanist and Effective Justice - Seniman Nainggola, Gunar; Kusbianto, Kusbianto; Trisna Dewi, Ayu (STAINI Press, 2026)
Mediation as part of the civil justice system in Indonesia has received juridical reinforcement through Supreme Court Regulation No. 1 of 2016 on Mediation Procedures in Court, which affirms the strategic role of non-judge mediators in resolving disputes amicably. This article aims to analyze the role of non-judge mediators following the enactment of Supreme Court Regulation No. 1 of 2016, identify opportunities and challenges in the implementation of court mediation, and assess their contribution to the efficiency of dispute resolution in order to realize a humanistic and effective judicial system. This study employs a normative legal method with statutory and conceptual approaches. The results indicate that non-judge mediators play a significant role in increasing the success of mediation through participatory and communicative approaches. Nevertheless, the optimization of their role still faces normative, structural, and cultural challenges, requiring regulatory reinforcement, enhancement of mediator competencies, and institutional support within the judiciary.